The usefulness of a single arm cuff oscillometric method (Arteriograph) to assess changes in central aortic blood pressure and arterial stiffness by antihypertensive treatment: results from the Doxazosin-Ramipril Study - Andreas Jekell; Thomas Kahan (Blood Pressure, 2018)
Purpose: Inhibition of the renin-angiotensin system may have effects on vascular structure and function beyond the effects on blood pressure (BP) reduction. We studied the ability of a single arm cuff oscillometric method (Arteriograph, TensioMed, Hungary) to assess effects of antihypertensive treatment on BP and arterial stiffness. Furthermore, this technique was compared to pulse wave analysis and applanation tonometry (SphygmoCor, AtCor Medical, Australia). Materials and methods: Brachial and aortic BP, augmentation index (AIx), and carotid-femoral pulse wave velocity (PWV) was simultaneously assessed by both techniques in 71 untreated hypertensive patients. Thereafter, 58 completed double-blind randomized treatment for 12 weeks with ramipril or doxazosin. Results: Treatment (assessed by the Arteriograph) reduced aortic more than brachial systolic BP (−13.2 vs. −11.2 mm Hg; p = .002) and improved all indices of arterial stiffness. This greater reduction in aortic to brachial systolic BP was more marked by ramipril than by doxazosin (−20.9 and −17.1 vs. −4.3 and −4.2 mm Hg; p = .006), with a similar trend for AIx (−6.2 vs. −2.2%; p = .058). Both devices showed correlations for aortic and brachial systolic and diastolic BP and AIx (r = 0.75–0.86, all p < .001), while agreement for PWV was weaker (r = 0.28; p = .043). The Arteriograph generally recorded higher values for aortic BP and AIx than the SphygmoCor. Conclusions: Antihypertensive treatment reduced aortic systolic BP more than brachial BP and improved arterial stiffness. Blocking the renin-angiotensin system may have additional effects beyond BP reduction. We demonstrate the feasibility of the Arteriograph to monitor changes in BP and arterial stiffness by treatment.